KONSEP DIRI PELAKU BODY FIT DI KOTA PEKANBARU - Meizar Fatahillah; Welly Wirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
One of indicator of beauty and handsome concept is an ideal figure that is resemble from a model image that much served in poster and celebrities magazine. Healthy life-style had been trend among people in Indonesia. Especially the people who leaves in big city. Trend body fit in now making ideal body as an icon and trendsetter which influence their paradigm and self concept in society. The progress of fit body phenomena very related to self concept of someone in appreciate himself and also the desire to be appreciated by peoples. The forming for ideal body though body fit could be said an information to attempted by the offenders to delivered about him self. A shifting in self concept could be seen in how they representated themselves from face to face or by social media. The purpose of this research is how self concept’s body fit in pekanbaru, how the motives the body fit offender sto get an ideal body. How is the self-pride before and after complied the body fit program. This research uses qualitative method with phenomenology approach. This research uses miles and hubermen’s interactive data analysis model, with the data validity examination technique through participation extension and triangulation. The subject of the this research is one of member prince gym in pekanbaru. The subject chosen by using purposive technique that is the writer decide to take by particular consideration. The result of this research indicates that body-fit’s offenders in pekanbaru is the body fit offender’s motives comply body-fit program want to support the work, changing appearance , psychological burden, and want to be healthy. Te image self of the offenders before complied body fit program which dominant in this research, view of it self doesn’t had confidence and always wore loose dress for the fashion style. The image-self of the offenders after comply body-fit program which dominant in this research view of it self more confidence and the slim fit for the fashion style. The self-pride’s offenders before complied the body fit program which dominant in this research, the undesirable body parts are arms and abdomen and the feeling of informer in the middle of crowd was uncomfortable. the self pride offenders before complied the body fit program which dominant by desirable body parts are arms and abdomen, and the feeling of informer on the middle of the crowd became comfortable. The expectation that appears from body-fit’s offenders in easy to get a job. Key word: Self-Concept, Phenomenology, Body Fi